BOOK REVIEW of NATIVE SON by RICHARD WRIGHT - Santika, Erfin baharina (LANTERN (Journal on English Language, Culture and Literature), 2014)
In NativeSon, Wright tells that Black do not have freedom as the Whites do.It also describes Black movement to show their protest against the White policies in America.Bigger Thomas is the main character of Native Son. The conflict inside the novel is institutionalizedracism in the United States as reflected in unequal education, unequal justice, and perpetuation of stereotypes of African-American people in the various media.In the last part of the story, Bigger kills Mary Dalton accidentally. Yet, Bigger uses the political purpose as a motif to hide his crime. Although Bigger takes advantages during his unknown crime, still he is sent to death by White’s court system.